Writing using blogs: a way to engage colombian adolescents in meaningful communication (2011)
We report an action research project developed with ninth grade students of a public school in Bogotá, Colombia, and which focused on innovating English communication through writing blogs. The project took into account the implementation of a specific blog that proposes activities, suggestions, strategies and links, among other things, to increase communication in English. It also prompted the written production of students in the blogs when posting entries and communicating through them. Some aspects of the project were developed in the classroom; others in the computers room, and others were developed by the students independently or collaboratively with classmates. Findings show how students communicated through writing in blogs and the main characteristics of the interaction that took place when using them.Reportamos un proyecto de investigación acción que se desarrolló con estudiantes de noveno grado de un colegio público de Bogotá, Colombia. En este proyecto se buscó innovar en el medio de comunicación en inglés a través de la escritura de bitácoras o blogs. El proyecto tuvo en cuenta la realización de una bitácora específica en la que se plantearon actividades, sugerencias, estrategias y enlaces, entre otros, para incrementar la comunicación en inglés. También motivó la producción escrita de los estudiantes en las bitácoras, al publicar entradas y comunicarse a través de estas. Algunos aspectos del proyecto se desarrollaron en el aula de clase; otros, en el aula de sistemas, o de forma autónoma y colaborativa con otros compañeros. Los resultados muestran cómo se comunicaron los estudiantes al escribir en las bitácoras, así como las principales características de la interacción que se generó.